Haemorrhoidectomy With and Without Lateral Internal Sphinterotomy - Muhammad Waqas Raza, Aurangzeb Khan , Raja Atif Kamran, Khurram Waqas , Azam Yusuf (Journal of Rawalpindi Medical College, 2013)
Background: To compare the two cohorts of patients in terms of postoperative pain after classical Milligan Morgan haemorrhoidectomy, with and without lateral internal sphinterotomy. Methods: In this comparative study, patients in age group of 18-70 years with intero-external and third degree haemorrhoids were included. Group A underwent open Haemorrhoidectomy by Milligan Morgan technique and Group B had haemorrhoidectomy with lateral internal sphinterotomy. Frequency of postoperative pain in both groups was compared at 48 hours, one week and after four weeks by visual analog scale. Results were compared using Chi Square test. Results: Total 108 patients were included in the study, 54 in open haemorrhoidectomy(group A) and another 54 in haemorrhoidectomy with lateral internal sphinterotomy(group B). Overall male predominance was found (64%). Patients in group B experienced less postoperative pain as compared to Group A. At the end of study number of patients who were completely pain free were 15 in group A and 38 in group B( p value=0 .000). Conclusion: Lateral internal sphinterotomy, combined with haemorrhoidectomy, is associated with less postoperative pain